Jens Rydström, Kati Mustola (ed.), Criminally Queer: Homosexuality and Criminal Law in Scandinavia (1842-1999) - Boukhris, Karim (Crime, Histoire & Sociétés, 2013)
Cet ouvrage consiste en une analyse comparative de l’évolution légale de la répression de l’homosexualité en Scandinavie. Pour chacun des sept États retenus (Danemark, Norvège, Islande, Groënland, îles Féroé, Suède et Finlande), le point de départ de l’étude se situe au moment où l’homosexualité n’est plus passible de mort (entre 1842 et 1894 selon les États). C’est un choix judicieux puisqu’il s’agit là d’une étape importante dans le processus de décriminalisation qui s’est achevé avec l’abo. This book consists of a comparative analysis of the legal development of the repression of homosexuality in Scandinavia. For each of the seven selected states (Denmark, Norway, Iceland, Groënland, Faroe Islands, Sweden and Finland), the starting point for the study is when homosexuality is no longer punishable by death (between 1842 and 1894 depending on the state). This is a sensible choice as this is an important step in the process of decriminalisation that has been completed with the abo.